Pelatihan Penyusunan Analisis Harga Satuan Pekerjaan (AHS) sesuai SNI di Desa Tongo Kecamatan Bonepantai Kabupaten Bone Bolango - Ervan Hasan Harun; Jumiati Ilham; Ifan Wiranto; Bambang Panji Asmara; Wahab Musa; Wrastawa Ridwan (Universitas Majalengka, 2023)
Increasing infrastructure through the allocation of village funds in the context of improving community services is increasingly being carried out in every region. Every year the allocation of village funds through the APBN continues to increase. Along with these efforts, village officials who are expected to be intermediaries for the implementation of the infrastructure improvement program are required to have the ability to carry out technical development implementation activities in the field. Tongo Village as a partner who cooperates in Community Service activities this time has been guided and trained through training activities using the learning by doing method related to Work Unit Price Analysis (AHSP) based on the Indonesian National Standard (SNI). The materials provided to village officials are: an introduction to the RAB and its constituent components, and Work Unit Price Analysis (AHSP) which consists of: work volume, estimated time for work completion, calculation of the number of workers and material requirements. From the results of the training it can be concluded that village officials understand how to make a Work Unit Price Analysis (AHSP) according to the Indonesian National Standard (SNI) using Microsoft Excel as the main component in the Budget Plan (RAB).